1964
DOI: 10.1136/gut.5.5.412
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer in India and its aetiology

Abstract: SYNOPSIS A study of the incidence of peptic ulcer amongst railway workers in various parts of India has shown that ulcer is more common in wet and humid areas than in the dry and arid regions. This observation is also supported by the ulcer incidence reported in other studies from India, Africa, and the West.Saliva appears to have an important role in the prevention of ulcer, because of its rich content of blood group antigens. There may be unrecognized factors in the saliva which may be ulcerogenic and others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…In the Western societies IBS is the commonest gastrointestinal syndrome. 15,16,17 IBS patients also complained of nocturnal pain. 9,11 Mean age of presentation of IBS was 30.43 years.…”
Section: Results and Observationsmentioning
confidence: 99%
“…In the Western societies IBS is the commonest gastrointestinal syndrome. 15,16,17 IBS patients also complained of nocturnal pain. 9,11 Mean age of presentation of IBS was 30.43 years.…”
Section: Results and Observationsmentioning
confidence: 99%
“…The results suggest that (1) the meal-mediated gastric acid secretory response in duodenal ulcer subjects is much higher than in the controls, even though the histamine stimulated response is similar, (2) the type of meal, whether rice and fish based or wheat and meat based, does not influence the acid secretory response, and (3) the duodenal ulcer subjects in this area, two hours after a meal, have a buffer capacity similar to the controls.Duodenal ulcer disease in the Indian subcontinent is more common in the rice-eating belt and uncommon in the wheat-eating areas (Malhotra, 1964). Our studies on in-vitro hydrogen ion binding by different cereals have shown that cooked wholewheat flour and cooked bran have a higher hydrogen ion binding capacity than cooked rice (Jalan et al, 1977).…”
mentioning
confidence: 75%
“…We have no accurate data with regard to maize consumption and a lower frequency of gastric cancers but the high incidence of these cancers among the South Indians does not support the thesis on potatoes, because in south India where these cancers are common the principal source of energy is boiled rice, ragi (Eulicine coracona), or tapioca and not potatoes (Malhotra, 1964;Indian Council for Medical Research, 1964).…”
Section: Causal Influences Cancers Of the Buccal Cavity And Oesophagealmentioning
confidence: 88%
“…not, therefore, account for these differences, because even though quid is an important ingredient of the betel leaf used in Mangalore, the Haryana region of the Punjab, and the Saurashtra regions, the incidence rates of these cancers are low in these areas. Chewing of betel nut and betel leaf, commonly known as paan, is a universal habit in India and the differences in the paans eaten in the various parts of the country have been described in an earlier communication (Malhotra, 1964). Two ingredients of the paan have as yet received insufficient attention, namely, the slaked lime solution, which is highly alkaline with a pH of 11.4 to 12.4, and Kattha (catechew) solution which has a pH of 3.2 to 4.2 depending upon the concentrations used.…”
Section: Causal Influences Cancers Of the Buccal Cavity And Oesophagealmentioning
confidence: 99%